2013
DOI: 10.1517/13543784.2014.844788
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific tolerization approaches in multiple sclerosis

Abstract: Introduction: Inhibition of self-reactive T cells through induction of antigen-specific immune tolerance holds the promise of effective treatment of autoimmune pathology with few side effects and preservation of normal immune functions. In multiple sclerosis (MS) several approaches have been tested already in clinical trials or are currently ongoing with the aim to inhibit myelin-reactive immune responses. Areas covered: This article provides an overview of the recent and ongoing strategies to inhibit specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 83 publications
1
50
0
Order By: Relevance
“…A limited number of self-reactive T cells escape the thymus and are present in the peripheral T-cell repertoire where they might become activated initiating autoimmune diseases. Inhibition of autoreactive T cells through induction of antigenspecific immune tolerance holds the promise of effective treatment of autoimmune pathology with few side effects and preservation of normal immune functions [110]. In MS, a number of different approaches have already been tested in clinical trials or in currently ongoing trials with the aim of inhibiting myelin-reactive immune responses.…”
Section: Future T-cell-directed Therapeutic Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…A limited number of self-reactive T cells escape the thymus and are present in the peripheral T-cell repertoire where they might become activated initiating autoimmune diseases. Inhibition of autoreactive T cells through induction of antigenspecific immune tolerance holds the promise of effective treatment of autoimmune pathology with few side effects and preservation of normal immune functions [110]. In MS, a number of different approaches have already been tested in clinical trials or in currently ongoing trials with the aim of inhibiting myelin-reactive immune responses.…”
Section: Future T-cell-directed Therapeutic Approachesmentioning
confidence: 99%
“…Different administration routes (intravenously, transdermally, intranasally, orally) have been assessed experimentally [111], and while all of them seem to achieve tolerance induction, different pathways seem to be involved, for example elimination of antigen-specific cells by induction of apoptosis or anergy, or induction of tolerogenic antigenspecific cells [110]. A number of attempts have so far been assessed in human trials.…”
Section: Myelin Peptide-based Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, an alternative treatment approach in MS could aim to selectively restore self-tolerance to auto-antigens via immunization [160] and epitope-specific induction of T cell tolerization [161] or specifically by targeting regulatory T cells (Treg) signaling [162]. Antigen-specific therapies in MS have been reviewed [163,164]. A first phase I trial in humans published in 2013 showed that the antigen-coupled cell tolerization in MS is feasible and safe [165].…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%